The role of organizational commitment mediation on the effect of compensation and motivation on performance - Sari, Rai Mutiara; Dewi, IGA Manuati (International research journal of management, IT and social sciences, 2020)
The purpose of this study is to analyze the mediating role of organizational commitment on the effect of compensation and motivation on performance. The study was conducted on Blue Bird Bali drivers with a population of 1090 drivers and took a sample of 235 drivers. Data collection was carried out by interviewing and distributing questionnaires using a 5-point Likert scale. The data analysis technique used is SEM-PLS. The results showed that compensation significantly and positively affected driver performance, motivation had a positive and significant effect on driver performance, the organizational commitment had a positive and significant effect on driver performance, compensation had a positive and significant effect on organizational commitment, motivation had a positive and significant effect on organizational commitment, organizational commitment has a partial mediating role in the relationship between compensation for driver performance and organizational commitment has a partial mediating role in the relationship between motivation and driver performance.